Democratic paths and trends - Wejnert, Barbara (Research in political sociology, 2010)
In this text, Research in Political Sociology: Democratic Paths and Trends, the imperative and current issues of democratic trends are presented by scholars from Asia, Europe, Latin America and the United States. The volume addresses worldwide changes and developments of democratization from historical and contemporary perspectives. It presents discourses on the diffusion of democracy, paths of democratic transitions, worldwide trends towards democratization, as well as discussion about democracy in retreat. Cross-cultural, comparative studies sit alongside case studies of individual countries including democratic development in the United States, post-colonial and post-Soviet democratization trends, and most recent experiences of countries that have undergone democratization growth or democracy in retreat in the first decade of this century. This volume can be used by political sociologists to strengthen and develop the unique skills and interests they bring to sociology. It is pertinent to researchers from political science, sociology, anthropology, economics, and to policy makers from across the globe working on democratic transition and democratization/re-democratization issues.